The Public and the Scene in Prison: How to evaluate the Spectator’s Participation in the performative Experiences of the Nuovo Teatro Galeotto in Bollate (Itinera, 2019)
To study spectators’ participation in performances by inmates, we must be able to analyse, process and evaluate, in both qualitative and quantitative terms, the data giving us the insight into the special nature and possible outcome of this relational experience. This is the aim of the Nuovo Teatro Galeotto project at the Bollate correctional facility underway between 2017 and 2018. Essentially, the intention is to define a system for evaluating theatre activities by the inmates, in order to fully understand their significance as part of projects designed to contribute the rehabilitation and social re-integration of people serving time in prison for various ‘antisocial’ acts, and to measure the effects of these activities on different audiences.